Evaluation of the Implementation of Community-Based Interventions (CBI) in Drug Abuse Prevention Programs in North Sumatra Province - Tiara Rajagukguk; Febriantika Febriantika; Laniah Lubis (Indonesian Journal of Global Health Research, 2024)
North Sumatra Province has the highest number of drug cases in Indonesia, with 2,049 cases until the first quarter of 2021. The dangers of drug abuse have spread to school-age children, based on the results of the 2021 BNN National Survey, there was an increase in drug exposure in the 15-24 year age group. The Community-Based Intervention (IBM) Program reflects the government's serious attention to efforts to deal with drug abuse in the community. Although since 2021 the North Sumatra BNNP has implemented the IBM program, the prevalence of drug abuse in North Sumatra Province is still high. Therefore, this study was conducted with the aim of 1) evaluating the effectiveness of the IBM program as a drug abuse prevention program. 2) to find out what are the inhibiting and supporting factors in implementing the IBM program . The research method used is a qualitative method that is evaluative in nature. Data collection uses three methods, namely observation, interviews and documentation. The selection of informants using the purposive sampling technique to be interviewed, namely the researcher selects informants who have the appropriate criteria to be interviewed. The theory used is the socialization theory by George Herbert Mead in analyzing and discussing the existing findings. The evaluation of the IBM program is expected to provide significant contributions to the literature on drug abuse prevention in the community and provide practical insights for Recovery Agents (AP), Practitioners, and BNN. The results of the study and discussion explain that 1) That the IBM program in the North Sumatra Province is quite effective, this is due to the maximum cooperation of the North Sumatra Province BNN with the community and Recovery Agents. 2 Internal barriers include lack of human resources, facilities, and program adjustments to the community. External barriers include social stigma, lack of family support, and environmental influences such as friends and drug dealers. Both of these factors hinder the effectiveness of rehabilitation programs.